Coloration patterns of marine sponges assessed by vibrational spectroscopy. (19th May 2021) - Maia, Lenize F.; Gonzaga, Tatiani A.; Campos, Mariana T. C.; Lobo‐Hajdu, Gisele; Edwards, Howell G. M.; de Oliveira, Luiz F. C.
Abstract: Sponges (phylum Porifera) are colorful filter feeding animals that harbor a large number of microorganisms in their tissue‐like structures in a symbiotic relationship. The colors exhibited by sponges implied in physiological and ecological process can be biosynthetically derived or acquired from the symbiont. In this work, the coloration pattern of nine species of sponges collected in the littoral of Rio de Janeiro State, Brazil, was identified by vibrational spectroscopy. An unprecedented study combining Raman and infrared spectroscopies revealed that carotenoids are responsible for the color of red‐orange, green, and blue species, while melanin was addressed to the black species. The analysis of the spectral features of Raman bands presented in both in situ and crude extracts samples showed that carotenoids may occur as a mixture of isomers or alternatively, be bonded to proteins (carotenoproteins). It is noteworthy that the carotenoid‐based pigmentation in sponges is provided by the symbionts, which may be implied to the evolutionary and ecological success of this most ancient animal. The application of vibrational spectroscopy mainly in the in situ mode can be a valuable tool in the identification of structural differentiation of carotenoids in the microbiome of sponges collected in different environments. Abstract : Coloration of nine species of sponges collected in the littoral of Rio de Janeiro State, Brazil, was identified by combining Raman and infrared spectroscopy. Both techniques showed that carotenoids occur in all surveyed species. The intensity ratios of carotenoid stretching modes (C=C)/(C–C) were used to distinguish orange derived color from the green and blue ones. Major spectral differences suggested the occurrence of carotenoids isomers or carotenoids bounded to proteins. The pigment of black species was addressed to melanin. ​